Clinical performance on dental mannequin and perceived clinical learning experience of left handed students at Kulliyyah of Dentistry, International Islamic University Malaysia - Ko, Bo Bo; Raid, Kais; Han, Tin Myo (IIUM Medical Journal Malaysia, 2016)
Introduction: Dental equipments are ergonomically designed for the right handed people. Hence left handed students have to adapt to use their right hands with their body position while treating the patients. Methods: It was a cross sectional comparative study. Ten left handed students and ten right handed students were invited for this study. The participants were randomly divided into 4 groups. They were assigned to do class I cavity preparation with the buccal extension and amalgam filling on the artificial tooth 36 on the dental mannequin. Group (1) the right handed students who worked from the right side of the mannequin with the right hand (n=10), group (2) the left handed students who worked from the right side of the mannequin with the right hand (n=10), group (3) the left handed students who worked from the right side of the mannequin with the left hand (n=10) and group (4) the left handed students who worked from the left side of the mannequin with the left hand (n=10). The quality of the cavity and amalgam filling were scored by the expert who had been blinded. Data were statistically analyzed by ANOVA test. The perceived clinical learning experience of left handed students was also evaluated by self administered questionnaires by using likert scales. Results: Mean score of clinical performance on the dental mannequins showed highest in group (4), P value =0.004. Conclusions: Left handed students should be allowed to work up to their hand preference and position